APPLICATION OF STRATEGIC ANALYSIS TOOLS FOR IDENTIFYING MAKRO ENVIRONMENTAL FACTORS: THE CASE OF STARTUP COMPANY CONNECTING CONSUMERS AND PRODUCERS OF ORGANIC AGRICURTULAR PRODUCTS VIA A MOBILE APPLICATION : DOI: 10.5937/etp2402059J - Janovac, Tatjana; Vukčević, Marijana (Ekonomija - teorija i praksa, 2024)
Start-up companies are generators of economic development. Given that these companies are characterized by a high degree of risk at the beginning of their operations, it is very important to properly formulate development and positioning strategies. This paper uses strategic tools to analyze the internal and external factors affecting the operations of a start-up company. The analysis of internal and external factors was carried out on the case of a start-up company established with the aim of connecting consumers and producers of organic agricultural products through a mobile application. The significance of this paper lies in providing guidelines to the company's management for defining business development and market positioning strategies. The results of this research serve as an incentive for further studies related to start-up companies, both at the local and regional levels.